Associations of exposure to volatile organic compounds with sleep health and potential mediators: analysis of NHANES data - Zhuang, Yan; Li, Laifu; Zhang, Yanqi; Dai, Fei (Frontiers in Public Health, 2024)
Objective:The effect of environmental pollution on sleep has been widely studied, yet the relationship between exposure to volatile organic compounds (VOCs) and sleep health requires further exploration. We aimed to investigate the single and mixed effect of urinary VOC metabolites on sleep health and identify potential mediators.Methods:Data for this cross-sectional study was collected from the National Health and Nutrition Examination Surveys (NHANES) (2005-2006, 2011-2014). A weighted multivariate logistic regression was established to explore the associations of 16 VOCs with four sleep outcomes. Following the selection of important VOCs through the least absolute shrinkage and selection operator (LASSO) regression, principal component analyses (PCA), weight quantile sum (WQS), and Bayesian kernel machine regression (BKMR) analyses were conducted to explore the associations between exposure to single and mixed VOCs and sleep outcomes, as well as identify the most contributing components. A mediation analysis was performed to explore the potential effect of depression scores.Results:Of the 3473 participants included in the study, a total of 618 were diagnosed with poor sleep patterns. In logistic regression analyses, 7, 10, 1, and 5 VOCs were significantly positively correlated with poor sleep patterns, abnormal sleep duration, trouble sleeping, and sleep disorders respectively. The PCA analysis showed that PC1 was substantially linked to a higher risk of poor sleep patterns and its components. The WQS model revealed a positive association between VOC mixture of increased concentrations and poor sleep patterns (OR (95% CI): 1.285 (1.107, 1.493)), abnormal sleep duration (OR (95% CI): 1.154 (1.030, 1.295)), trouble sleeping (OR (95% CI): 1.236 (1.090, 1.403)) and sleep disorders (OR (95% CI): 1.378 (1.118, 1.705)). The BKMR model found positive associations of the overall VOC exposure with poor sleep patterns, trouble sleeping, and sleep disorders. PCA, WQS, and BKMR models all confirmed the significant role of N-acetyl-S-(N-methylcarbamoyl)-L-cysteine (AMCC) in poor sleep patterns and its components. The depression score was a mediator between the positive VOC mixture index and the four sleep outcomes.Conclusion:Exposure to single and mixed VOCs negatively affected the sleep health of American population, with AMCC playing a significant role. The depression score mediated the VOC mixtures and sleep health.